2008
DOI: 10.1016/j.neuroscience.2007.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the protein synthesis inhibitor, anisomycin, has distinct sleep-promoting effects in lateral preoptic and perifornical hypothalamic sites in rats

Abstract: Although a robust relationship between sleep and increased brain protein synthesis is welldocumented, there have been few reports of the effects of local application of a protein synthesis inhibitor (PSI) on sleep. In this study, we compared the effects of local microdialytic administration of the protein synthesis inhibitor, anisomycin (ANI) into the lateral preoptic area (LPOA), a sleep promoting area vs. the perifornical/lateral hypothalamus (PF / LH), a wake and rapid eye movement (REM) sleep-promoting are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Gene expression studies have suggested that protein synthesis is up-regulated during sleep [2] , [58] , which may be an essential stage in macromolecular biosynthesis [59] [61] . Consistent with this, inhibiting protein synthesis in specific brain domains prolongs sleep duration in mammals, suggesting that sleep is maintained until specific levels of biosynthesis occur and aids in explaining the ubiquitously conserved need for sleep [37] , [62] . Here, brief cycloheximide treatment prolonged night sleep and increased consolidation in flies, indicating an evolutionarily conserved role for protein synthesis inhibition on sleep regulation.…”
Section: Discussionmentioning
confidence: 68%
“…Gene expression studies have suggested that protein synthesis is up-regulated during sleep [2] , [58] , which may be an essential stage in macromolecular biosynthesis [59] [61] . Consistent with this, inhibiting protein synthesis in specific brain domains prolongs sleep duration in mammals, suggesting that sleep is maintained until specific levels of biosynthesis occur and aids in explaining the ubiquitously conserved need for sleep [37] , [62] . Here, brief cycloheximide treatment prolonged night sleep and increased consolidation in flies, indicating an evolutionarily conserved role for protein synthesis inhibition on sleep regulation.…”
Section: Discussionmentioning
confidence: 68%
“…Administration of protein synthesis inhibitors (PSIs) usually increases NREM sleep but reduces REM sleep (33). Recently, we reported (26) that local administration of the PSI anisomycin (Ani) induced site-specific facilitation of sleep states. NREM sleep was increased by Ani administration in the lateral preoptic area and REM sleep by administration in the perifornical hypothalamic areas of rats.…”
mentioning
confidence: 99%
“…A surge in GH release occurs early in the major circadian sleep period in humans and in rats, specifically during the earliest stage 3/4 NREM sleep episodes in humans. 87 GHRH is proposed to be one element of a multiple-element sleeppromoting system. Neurons in the latter location are thought to be the source of projections to the POA and basal forebrain.…”
Section: Growth Hormone-releasing Hormonementioning
confidence: 99%